On the countability of the number of solutions of a two-dimensional linear Pfaff system with different characteristic sets - Izobov, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove that a two-dimensional, completely integrable, linear Pfaff system has at most countably many solutions with all different characteristic sets.